Time-varying Limit Order Book Networks - Wolfgang Karl Härdle; Shi Chen; Chong Liang; Melanie Schienle (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
This paper analyzes the market impact of limit order books (LOB) taking crossstock effects into account. Based on penalized vector autoregressive approach, we aim to identify significance and magnitude of the directed network channels within and between LOBs by bootstrapped impulse response functions. Moreover, information on asymmetries and imbalances within the LOB over time would be derived. For the sample of a NASDAQ blue-chip portfolio during 06-07/2016 we find that LOB network effects crucially determine prices and bid-ask asymmetries are prevalent.
Keywords: C02; C13; C22; C45; G12; 330; limit order book; high dimension; generalized impulse response; high frequency; market risk; market impact; network; bootstrap